Academic freedom and dual career academic couples: the complexities of being a woman academic in the university space (2010)
This study focuses on dual career women academics in a higher education (HE) institution in Nigeria. It explores the experiences of some of these women academics and exposes the internal dynamics that characterize intra-group interactions in the academe. It subsequently raises the issue of equitable participation of men and women academics in HE institutions in Africa. It attempts to understand how the constructed identities of dual career women academics intersect with their interactions in the university space, and impact on their career experiences. Paying attention to the marital institution also, this study explores how these women’s academic freedom can be undermined by the power play in this arena, bearing in mind their categorization. The study thus identifies the areas in which the autonomy and academic freedom of women academics in dual career marriages are possibly undermined. Ethnographic methods provided data for this study. The article concludes that the challenge of academic freedom demands more inward examination of the ‘micro politics within’ in order to incorporate the interests of all stakeholders within the intellectual community in the struggle for academic freedom and academic democracy in the continent of Africa.